Strategi Petani Sawah Dalam Upaya Pemenuhan Kebutuhan Hidup (Studi Pada Masyarakat Petani Penggarap di Desa Paccellekang Kecamatan Patalassang Kabupaten Gowa) - Abdul Muin (Phinisi Integration Review, 2022)
In this study, the aim of this study was to see how the farmers' strategies or methods were used to meet the needs or survival that occurred to smallholders in Paccelekang Village, Patalassang District, Gowa Regency. This study uses a qualitative method. This research is located in Paccelekang Kacan Patalassang Village. The instrument in this study used observation and interviews. Furthermore, this study uses a triangulation and interaction model approach aimed at analyzing the data obtained from existing research. The results of this study indicate that the Rice Farmer's Strategy in Efforts to Fulfill the Living Needs of Cultivators in Paccellekang Village, Patalassang District, Gowa Regency, there are 2 forms of farmers, namely farmers working on upper level and middle level rice fields. Upper-level cultivators have the advantage that their large farm gardens can raise cattle. Meanwhile, the middle-level farmers from the agricultural products they get are only able to meet the daily needs of their families because they work on their plantations from their own land. However, the advantages of these farmers are that they are able to build strong social relations and relationships with fellow farmers and outside of farmer workers. From the education sector, on average, these farmers only graduated from junior high and high school, but with the times, farmers have started to care about the existing level of education. This is shown by the children of several farmers who have started their education up to the tertiary level and even at the master's level.